EFFECT OF WORK TRAINING, WORK MOTIVATION, AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT PT. X - Syahrian Syahrian; Dimas Prakoso (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Abstract This study aims to determine the effect of job training, work motivation, work discipline on employee performance. This research was conducted at PT. X, by taking 80 employees as research samples using a probability sampling technique, namely proportionate stratified random sampling. Collecting data using observation and questionnaire methods. Data analysis technique collected using multiple regression analysis. Based on the studies conducted, the research results show that job training, work motivation, and work discipline have an influence on employee performance. Keywords: Work Training, Work Motivation, Work Discipline, Employee Performance.